Consolidation of Specific Items of Financial Statements of Company Group: Principles, Conditions and Features - I. M. Dmytrenko (Статистика України, 2019)
The impact of the adequacy of the application of the basic principles, conditions and order of consolidation by a company group, to ensure the reliability of the most specific items of financial statements, is considered as a subject matter of internal and external auditors. The components of the consolidated financial statements, its structural elements, specific items and a set of necessary disclosures in the notes are distinguished on the basis of comparative analysis. The conditions for the parent company’s control as an investor over the activities of its subsidiaries as an investee for the purpose of applying the consolidation procedure are systematized. The prerequisites for ensuring the reliability of the consolidated reporting information are generalized. The characteristics of these prerequisites are given in view of the parent company’s ownership of a certain share of the net assets of the subsidiaries at the reporting date and its investments in the subsidiaries during the reporting year with their inclusion in the book value. The necessary emphasis is placed on the proper disclosure of information about all subsidiaries in accordance with the principles of financial reporting. The subject area of internal and external audit is analyzed with focus on the most specific items of the consolidated financial statements: uncontrolled interest, goodwill and intra-group transactions. The factors for minimizing the risk of distortion at the level of individual articles and the consolidated financial statements of a company group as a whole are identified. The instruments of ensuring the proper degree of completeness and reliability of disclosure in the consolidated statements of a company group in accordance with the requirements of international financial reporting standards are considered. In particular, the specificity of the disclosure of the influence of related parties on the profit, loss and financial position of the group is discussed. The pragmatic value of disclosures is determined in view of providing users with consolidated financial statements that are transparent and relevant to economic decision making.